PENGARUH MODEL MASTERY LEARNING TERHADAP EFEKTIVITAS PEMBELAJARAN PASSING BAWAH BOLAVOLI (STUDI PADA SISWA KELAS XI SMA NEGERI 1 PACET) - RISTYANINGTYAS, SEPTIALINDA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The purpose of this study was to determine the effect of mastery learning model to study the effectiveness of under passing the volley ball. With descriptive quantitative research design randomized control group posttest only design. This study used cluster random sampling for sampling and obtained class XI IPA 1 totaled 39 students as the experimental group and class XI IPS 1 totaled 38 students as a control group by calculating the average (mean), standard deviation, variance, normality test homogeneity, and t test. The research instrument used was formative class evaluation (FCE) and passing the learning outcomes. Results showed that both groups have the FCE questionnaire mean the same overall result is a value of 4, good category. Based on the study, the percentage of student graduating KKM control group 81.58%, 94.87% experiments. Percentage based on t test results are an increase in the effectiveness of learning under passing 2.59%. Keywords: Mastery learning model, Effectiveness, Under Passing.